Al-Qur’an dan Tiga Kitab Suci Samawi Lainnya - Nunung Lasmana; Ahmad Suhendra (Jurnal Asy-Syukriyyah, 2017)
One of the pillars of faith in Islam is to believe in the scriptures. The sacred scriptures are Zabur, Torah, Gospel and the Qur'an. The Qur'an as the last holy book also has acknowledged and confirmed the existence of the earlier books. the scriptures are not confined to the Qur'an alone, but other books are also kalamullah, such as Zabur, Torah, Gospel, and suhuf Prophet Ibrahim As. and the prophet Moses. as Allah mentioned in the Qur'an. That is why we are obliged to believe in these celestial books by believing wholeheartedly that the books have been sent down to His apostles. As for any change or deviation occurring against the earlier books then it is not something we should be faithful but rather the opposite.